Degraded Forest Evaluation Using Vegetation Indices at Bandealit Resort, Meru Betiri National Park - Mulyadi, Budi Putra; Sulistiyowati, Hari; Wimbaningrum, Retno (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2025)
The forest degradation and deforestation was widely occurred in Indonesia and Meru Betiri National Park is one of the area with illegal loggings threats. Bandealit Resort as one of the resort in Meru Betiri National Park was reported as the area with high activity of illegal loggings specifically in 2020. Based on this information, this research study aims to evaluate the degraded level of the forests using Normalized Difference Vegetation Index and Enhanced Vegetation Index (NDVI and EVI) so it can be managed and evaluated in the future. This research use direct and indirect observation methods in three areas with different damage levels. Direct observation was done by counting the number of species and the stands trees, while the indirect observation was analyzing the Landsat 8 Imagery in 2020, 2021 and 2022. The results showed that the A area had the lowest density with only 45 remaining trees than two others with more than 150 trees. The greenness levels imply the quality level of tree stand density, as higher the tree stand density, the higher the greenness. NDVI and EVI showed that A area had the range from low greenness (sparse density) to high greenness (medium density) than two others area had the higher greenness and densities.